Intraoperative radiotherapy (IORT) as boost in breast cancer. Issue 1 (December 2017) - Sedlmayer, Felix; Reitsamer, Roland; Wenz, Frederik; Sperk, Elena; Fussl, Christoph; Kaiser, Julia; Ziegler, Ingrid; Zehentmayr, Franz; Deutschmann, Heinz; Kopp, Peter; Fastner, Gerd
Abstract The term IORT (intraoperative radiotherapy) is currently used for various techniques that show huge differences in dose delivery and coverage of the tissue at risk. The largest evidence for boost IORT preceding whole breast irradiation (WBI) originates from intraoperative electron treatments (IOERT) with single doses around 10 Gy. At median follow-up periods at 6 years, outstandingly low local recurrence rates of less than 1% are observed. Higher local relapse rates were described for G3 tumors and triple negative breast cancers as well as for IORT following primary systemic treatment for locally advanced tumors. Even there, long term (>5y) local tumor control rates mostly beyond 95% were maintained. Compared to other boost methods, an intraoperative treatment has evident advantages in terms ofprecision (by avoiding a "spatial and/or temporal miss"), cosmetic outcome and patient comfort. Direct visualisation of a tumor bed during surgery guarantees for an accurate dose delivery, which has additionally gained importance in times of primary reconstruction techniques after lumpectomy, since IORT is performed before breast tissue including parts of the tumor bed is mobilized for plastic purposes. As a consequence of direct tissue exposure without distension by hematoma/seroma, IORT allows for small treatment volumes and complete skin sparing, both having a positive effect on late tissue tolerance and, hence, cosmetic appearance. Boost IORT marginally prolongs the surgical procedure, while significantly shortening postoperative radiotherapy. Its combination with external beam radiotherapy to the whole breast (WBI) is currently tested in two multicentric prospective trials: as kV-IORT in the multicentric TARGIT-B (oost) study, and as IOERT in the HIOB trial (3 weeks hypofractionated WBI preceded by IORT electron boost).